Prevalence and distribution of functional splenic tissue after splenectomy. Issue 5 (19th May 2020) - Luu, Sarah; Sheldon, James; Dendle, Claire; Ojaimi, Samar; Jones, Penelope; Woolley, Ian
Abstract: Background: Individuals splenectomised for trauma have lower infection rates than those splenectomised for other conditions. Residual functional splenic tissue (FST) after splenectomy may provide ongoing immunological protection. Aims: To quantify the prevalence and volume of residual FST post‐splenectomy using standard testing. Methods: Splenectomised adults were recruited from the Spleen Australia clinical registry. Eligible individuals had been splenectomised at least 1 year prior to their visit and resided in Victoria. Splenic function was identified by evaluating Howell–Jolly bodies and IgM memory B cells. A 99m‐Technetium‐labelled, heat‐denatured erythrocyte scintigraphic scan was performed if splenic function was detected. Results: Initially, 75 splenectomised individuals (all cause) were recruited, with a median of 58 years of age and who were splenectomised a median of 14 years previously. The most common indications for splenectomy were trauma (30.7%) and haematological disease (28.0%). Scintigraphy identified FST in nine individuals (12.0%). Eight had been splenectomised for trauma. In this cohort, 34.8% of individuals splenectomised for trauma had residual FST. To explore our findings further, 45 additional individuals were recruited, predominately individuals splenectomised for trauma. Twenty‐five individuals completed assessments by December 2018. An additional 11 individuals had FST, of whom 9 had been splenectomised for trauma. Overall, we identified 20 individuals with residual FST. Volumes ranged from 2.2 to 216.0 cc. We saw individuals with accessory spleens and splenotic nodules and an individual with both. Seventeen individuals had been splenectomised for trauma. Conclusions: Residual FST is commonly seen in individuals splenectomised for trauma. It can present in varying distributions and of varying volume. The clinical significance is unclear.